INVESTMENT ACTIVITY AND FACTORS INFLUENCING THE ATTRACTION OF FOREIGN ACTIVITIES IN THE REPUBLIC OF UZBEKISTAN (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article is explained investment activity and factors influencing the attraction of foreign activities in the Republic of Uzbekistan, main trends attracting foreign investments into the economy of Uzbekistan, also analyzed dynamics of the influence of investments in fixed assets on the development of the economy and social sphere of the Republic of Uzbekistan.